Electrocatalytic Reduction of CO2 in Water by a Palladium-Containing Metallopolymer - Teixeira, Marcos F. S. [UNESP]; Olean-Oliveira, André [UNESP]; Anastácio, Fernanda C. [UNESP]; David-Parra, Diego N. [UNESP]; Cardoso, Celso X. [UNESP] (MDPI, 2022)
The palladium–salen complex was immobilized by electropolymerization onto a Pt disc electrode and applied as an electrocatalyst for the reduction of CO2 in an aqueous solution. Linear sweep voltammetry measurements and rotating disk experiments were carried out to study the electrochemical reduction of carbon dioxide. The onset overpotential for carbon dioxide reduction was approximately −0.22 V vs. NHE on the poly-Pd(salen) modified electrode. In addition, by combining the electrochemical study with a kinetic study, the rate-determining step of the electrochemical CO2 reduction reaction (CO2 RR) was found to be the radial reduction of carbon dioxide to the CO adsorbed on the metal.
Keywords: aqueous system; electrocatalysis; electroreduction of dioxide carbon; metallopolymer; overpotential